Investing in infrastructure : What is Needed from 2000 to 2010? - Fay, Marianne; Yepes, Tito (World Bank, Washington, DC, 2014)
The authors estimate demand for infrastructure services over the first decade of the new millennium based on a model that relates demand for infrastructure with the structural change and growth in income the world is expected to undergo between now and 2010. It should be noted that predictions are based on estimated demand rather than on any absolute measure of "need" such as those developed in the Millenium Development Goals. The authors also provide estimates of associated investment and maintenance expenditures and predict total required resource flows to satisfy new demand while maintaining service for existing infrastructure.